THE MONITORING OF DANGEROUS SLIDING PROCESSES USING THE REMOTE SENSING DATA AND GEOPHYSICAL INVESTIGATIONS (ON EXAMPLE OF RIGHT BANK TERRITORY OF KYIV CITY OVER DNIPRO RIVER) - VYZHVA, S.; MYKOLENKO, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
Results of activity on development of the system for geophysical monitoring of dangerous sliding processes using the geoinformation systems and the Remote Sensing data are represented.